Naegeli-Franceschetti-Jadassohn syndrome: A rare reticulate pigmentary disorder - Gitika Sanodia; Manjunath Hulmani; V Jagannath Kumar (Wolters Kluwer Medknow Publications, 2019)
Naegeli-Franceschetti-Jadassohn syndrome is a rare autosomal dominant form of ectodermal dysplasia affecting sweat glands, nails, teeth, and skin. We report a case of 16-year-old female who had generalized reticulate pigmentation, dental changes, nail changes, and absence of dermatoglyphics and hypohydrosis.